TEOLOGI AL-MA’UN PERSPEKTIF NEUROSAINS: STUDI KASUS DI LKSA PANTI ASUHAN MUHAMMADIYAH WATES - Puspita Winatakina; Suyadi Suyadi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
The purpose of this study was to analyze al-Ma'un's theology from a neuroscience perspective that occurred at the Muhammadiyah Wates Orphanage. The research approach used is descriptive qualitative and field research, with library research method. This research discusses Al-Ma'un Theology which is one of the Muhammadiyah movements taught by KH. Ahmad Dahlan which is translated into three pillars, namely education (Schooling), health (healing), and social services (feeding). From there, we need the concept of mind or qalb, and spirit in realizing the theology of al-Ma'un. Because in neuroscience the metaphysical concept of the brain will optimize various human potentials. Neuroscience also examines the brain's awareness and sensitivity in terms of biology, perception, memory, and its relationship to learning. Religious learning that is carried out repeatedly at the Muhammadiyah Orphanage LKSA makes the brain work easier, this happens because the brain already knows from which basket the data related to the lesson must be taken so that it can understand a complete knowledge even up to saturation point.